Persepsi Mahasiswa Tingkat Menengah terhadap Perubahan Frekuensi dan Waktu Titik Lekuk Nada Turun-Naik Bahasa Mandarin - Nanda Lailatul Qadriani; Tri Budianingsih (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2021)
The tone is a phonetic characteristic of Chinese which is very important to master because it has a meaning-distinguishing function. For Indonesian students, Chinese tone, especially tone 2 and tone 3 is quite difficult to master both in perception and pronunciation. This study aims to measure the level of sensitivity and type of perception of students with intermediate level Chinese language proficiency in distinguishing tone 2 and tone 3. The tone or sound stimulus used in this study are fluctuating tones (降升调) which is the basic form of the second and third tones by varying the frequency and time of the curve point. The research method used is the experimental method, a research instrument based on a test. The results showed that changes in the high frequency and time of curve point in fluctuating sound stimulus had a significant effect. Respondents were more sensitive to changes in sound stimuli with the independent variable time of the curve point compared to the high frequency. The type of respondent's perception of the sound stimulus with the time-independent variable at the curve point is categorized as categorical perception. Meanwhile, the respondent's perception of the sound stimulus with the high-frequency independent variable at the curve point is classified as the continuous perceptionKeywords – Categorical perception, Continuous perception, Chinese phonetic, Chinese tone